Caracterização de scaffolds a base de colágeno tipo I aniônico visando tratamento de lesões na pele - Campos, Jessica Valéria de (2022)
Skin lesions can reach different intensities along the tissue, being the deepest those that affect all layers of the skin (epidermis, dermis and hypodermis), hampering the self-healing natural process. These make it essential use dressings to help the healing of the region. The need for dressings that simulate the tissue environment of the skin has driven studies in the field, being one of the main areas associated with tissue engineering, with a growing development in the use of biomaterials for making compatible structures such as the scaffolds. Type I collagen, due to its excellent biological properties such as biocompatibility, biodegradability and cell affinity, has been widely used in the processing of scaffolds for various applications, and mainly for skin regeneration. In the present work, the scaffolds were prepared in partnership with the company Jhaady Indústria e Comércio (São Carlos, SP) using type I collagen extracted from serous swine, in four extraction times (24, 48, 72 and 96 hours) by the method of selective hydrolysis, and using the casting technique in three different suspension medium (phosphate buffered saline 10 times concentrated, phosphate solution once concentrated and acetic acid), followed by lyophilization, giving rise to eight different types of scaffolds named S24hPB, S24hPBf, S48hPB, S48hPBf, S72hf, S72hAc, S96hf and S96hAc, according to the extraction time and suspension solution used. The physical-chemical evaluations of the scaffolds and samples of a commercial product Chondro-gide (Geistlich Pharma, Switzerland), provided data from scanning electron microscopy (SEM) making it possible to investigate the structure regarding the presence, distribution and size of pores, as well as porosity, in addition to the temperature required for denaturation (Td) of collagen by means of differential scanning calorimetry (DSC), in addition to analyzes of hydration capacity and hydrophilicity by contact angles measurements. The biological part, related to in vitro growing studies consisted in the inoculation of 1x106 mesenchymal stromal cells (MSCs) and cultures for 8, 12, 72 and 168 hours, associated with methods of analysis of cell counting by hemocytometer, analysis of nutrients (glucose and lactate) and scaffolds growth estimation by nutrient quantification, which together allowed us to selected four scaffolds (S48hPB, S48hPBf, S72hf and S96hf), as the most efficient in the cell culture growth. These scaffolds and the commercial sample (Chondro-Gide) were also tested with keratinocytes and fibroblasts, allowing observing cell adhesion and growth on the surface through SEM analysis, and the distribution of cells along the matrices of each sample by confocal fluorescence microscopy. In addition, quantitative cell growth data demonstrated that all samples show similar or higher efficiencies in cell adhesion and growth than Chondro-Gide, as samples S48hPB, S48hPBf, S72hf and S96hf. Thus, our study presents materials with physicochemical and biological characteristics suitable for cell growth and indicated for use in tissue engineering, in particular in the treatment of skin lesions.